Technological innovation and the complexity of imported technology: Moderating effects based on environmental regulation - Gao, Xin; Dong, Zhaoyan (Frontiers in Environmental Science, 2022)
Import technology complexity is an essential form of optimizing import trade structure. Achieving high-quality import opening through import technology complexity under the background of stricter environmental regulations and the increasing urgency of technological innovation has essential theoretical and practical significance. Given this, based on multiple database matching, this paper studies the effect of technological innovation on import technology complexity and the mechanism of environmental regulation on this effect from the dimension of provincial-import source-manufacturing products (HS6). The results show that technological innovation has a positive effect on the technical complexity of product imports, and the intensity of environmental regulation can strengthen the above effect. The moderating effects of environmental regulation show significant and different strengthening effects at regional,and industry levels.The strengthening effects are more important in eastern China and high pollution industries. These conclusions provide a theoretical and empirical basis for encouraging technological innovation and introducing differentiated environmental policies.